Fecal microbiota transplantation and bacterial consortium transplantation have comparable effects on the re-establishment of mucosal barrier function in mice with intestinal dysbiosis - Li, Ming; Liang, Pin; Li, Zhenzhen; Wang, Ying; Zhang, Guobin; Gao, Hongwei; Wen, Shu; Tang, Li (Frontiers in Microbiology, 2015)
Fecal microbiota transplantation (FMT) is a promising therapy, despite some reports of adverse side effects. Bacterial consortia transplantation (BCT) for targeted restoration of the intestinal ecosystem is considered a relatively safe and simple procedure. However, no systematic research has assessed the effects of FMT and BCT on immune responses of intestinal mucosal barrier in patients. We conducted complementary studies in animal models on the effects of FMT and BCT, and provide recommendations for improving the clinical outcomes of these treatments. To establish the dysbiosis model, male BALB/c mice were treated with ceftriaxone intra-gastrically for 7 days. After that, FMT and BCT were performed on ceftriaxone-treated mice for 3 consecutive days to rebuild the intestinal ecosystem. Post-FMT and post-BCT changes of the intestinal microbial community and mucosal barrier functions were investigated and compared. Disruption of intestinal microbial homeostasis impacted the integrity of mucosal epithelial layer, resulting in increased intestinal permeability. These outcomes were accompanied by overexpression of Muc2, significant decrease of SIgA secretion, and overproduction of defensins and inflammatory cytokines. After FMT and BCT, the intestinal microbiota recovered quickly, this was associated with better reconstruction of mucosal barriers and re-establishment of immune networks compared with spontaneous recovery (SR). Although based on a short-term study, our results suggest that FMT and BCT promote the re-establishment of intestinal microbial communities in mice with antibiotic-induced dysbiosis, and contribute to the temporal and spatial interactions between microbiota and mucosal barriers. The effects of BCT are comparable to that of FMT, especially in normalizing the intestinal levels of Muc2, SIgA, and defensins.